Access to and Repayment of Agricultural Credit in the Face of COVID 19: A Gender Analysis in Selected Microfinance Institutions in Cameroon - Shillie, Peter Ngek; Bime, Mary-Juliet Egwu; Balgah , Roland Azibo; Wiysherinyuy, Miranda Lambiv (Finance & Economics Review, 2022)
Purpose: Gender differences in access to and repayment of loans seem to be the reason behind the persistent subsistence and small-scale nature of most agribusinesses in Cameroon. This study examines access to and repayment of agricultural credit in the face of COVID 19 in the West Region of Cameroon building on evidence from selected microfinance institutions in the West Region of Cameroon. Specifically, the study mirrors gender differences in microfinance loan disbursements and repayments, determinants of loan repayment, and constraints to loan access and loan repayment during the period of COVID 19. Method: The purposive sampling technique was employed to select 100 farmers who had access to agricultural credit in three villages in the West Region of Cameroon. A pre-tested questionnaire was used for primary data collection and secondary data was collected from microfinance institutions and the internet. Collected data were analyzed employing tables, frequencies, t-test, and regression analysis. Results: Findings indicated that there was a positive insignificant difference in the amount of credit received and repaid by male farmers than that of the female farmers. The male and female have equal access to credit and the same repayment capacities (R2 = 0.55 or 55%). Loan repayment was statistically and significantly determined by loan amount, interest rate, and time lag for repayment at the 5% significance level. Serious constraints to loan access were lack of sensitization, lack of collateral security, and illiteracy while major constraints to loan repayment were family commitment, price fluctuation, crop failure, high cost of production, and interest payment. Implications: Increasing the ceiling for loan amount approved for farmers and curbing excessive bureaucratic procedures would ensure minimal diversion of the loans, higher income for the farmers, and hence better repayment rates. Originality: The distinctiveness of this study is viewed from the context of the COVID 19 pandemic within which data was collected, thus capturing how the pandemic situation played a role in access to and repayment of agricultural loans from the perspective of gender.